Exploring Fidelity in School-Based Mindfulness Programs. (12th December 2021) - Broderick, Patricia C.; Schussler, Deborah L.
A small but growing body of research on school-based mindfulness programs (SBMPs) has demonstrated benefits for students' cognitive and affective functioning and overall wellbeing. Yet, lack of fidelity in SBMP implementation may diminish these programs' purported benefits. This commentary presents 4 current challenges that need to be addressed so that questions of whether and how mindfulness improves student functioning can be clarified and implementation of programs can be strengthened and sustained. These challenges include coming to consensus on the definition and intention of mindfulness training, balancing adherence with flexibility in SBMP delivery, determining the role SBMP teachers' mindfulness experience plays in program fidelity, and delineating distinctive features of mindful pedagogy. Some suggestions for addressing each of these challenges are provided.